Wnt signaling from Gli1-expressing apical stem/progenitor cells is essential for the coordination of tooth root development - Lav, Rupali; Krivanek, Jan; Anthwal, Neal; Tucker, Abigail S (Stem cell reports, 2023)
Stem cell regulation plays a crucial role during development and homeostasis. Here, an essential source of Wnts from Gli1+ stem/progenitor cells was identified in the murine molar. Loss of Wnt production in Gli1+ apical stem/progenitor cells led to loss of Axin2 at the root apex, mis-regulation of SOX9, loss of BMP and Hh signaling, and truncation of root development. In the absence of Wnt signals, the root epithelium lost its integrity and epithelial identity. This phenotype could be partially mimicked by loss of Sox9 in the Gli1 population. Stabilization of Wnt signaling in the apical papilla led to rapid unordered differentiation of hard tissues and fragmentation of the epithelial root sheath. Wnt signaling from Gli1+ stem/progenitor cells, therefore, orchestrates root development, coordinating mesenchymal and epithelial interactions via SOX9 to regulate stem/progenitor cell expansion and differentiation. Our results demonstrate that disparate stem/progenitor cell populations are unified in their fundamental signaling interactions.
Keywords: Hh signaling; Wnt signaling; Zinc Finger Protein GLI1; myši; stem cells; tooth development; Tooth Root; protein Gli1; Wnt Signaling Pathway; kmenové buňky; tooth defects; Mice; Animals; homeostasis; Cell Differentiation; zubní kořen; zvířata; Stem Cells; buněčná diferenciace; development; signální dráha Wnt; Sox9